The AMBIT approach: working with hard to reach youth. Issue 1 (14th March 2016) - Fuggle, Peter; Bevington, Dickon; Duffy, Fiona; Cracknell, Liz
Abstract : Purpose: – MBIT is a manualised mentalization-based approach to working with hard to reach young people at risk of a wide range of life adversities including severe mental illness, substance misuse, family breakdown, school exclusion, offending and homelessness. The on-line manual (www.tiddlymanuals.com ) describes how Adolescent Mentalization-Based Integrative Therapy (AMBIT) is a systemic intervention requiring attention to four different domains of intervention simultaneously; much emphasis is placed on the support systems for workers to maintain this balance in what are often chaotic working conditions. The purpose of this paper is to illustrate how these four main components of the AMBIT approach link together in actual clinical practice. Design/methodology/approach: – The authors illustrate the core techniques of the AMBIT approach, namely, "working with your client", "working with your team", " working with your network" and "learning as a team" with a series of case vignettes, demonstrating the inter-relationship of these components rather than seeing them as separate strands. Findings: – A range of mentalization-based techniques such as "thinking together", mentalized formulation, "disintegration grids" and web-based manualising are described and illustrated in relation to a series of case vignettes in order to address barriers to effective practice. The vignettes emphasise how these components must be linked together and held in balance, and how easily they become disconnected in working with young people's ambivalent or even hostile relationships to help. Practical implications: – First, developing a shared, mentalized formulation of a young person's difficulties is an important aspect of working with highly troubled young people. Second, mentalizing is a relational process and is easily disrupted, for both workers and young people, by raised anxiety and affect, a common feature of working with this client group. AMBIT provides specific methods, for example, "thinking together" for supporting the mentalizing of individual workers in their team in an explicit way. Third, workers from different agencies may often find it difficult to make sense of each other's behaviour and decision making. AMBIT proposes the use of a mentalizing approach to this difficulty using a technique called a disintegration grid. Finally, AMBIT proposes a new practitioner focused approach to manualising as a method by which a team can become more explicit about its methods of working in order to support systematic practice and evaluate outcomes. Originality/value: – The innovative AMBIT approach proposes that clinicians need to attend to team and network relationships at least as much as their relationship with the client, in addition to adopting a stance of learning as a team from their casework. A high level of clinical skill is needed to support a team to achieve this balanced approach to casework. This work is of interest to all multi-disciplinary teams working with hard to reach young people.